Review of the safety, efficacy and patient acceptability of the combined dienogest/estradiol valerate contraceptive pill - Maurizio Guida; Giuseppe Bifulco; Attilio Di Spiezio Sardo; et al (Dove Medical Press, 2010)
Maurizio Guida, Giuseppe Bifulco, Attilio Di Spiezio Sardo, Mariamaddalena Scala, Loredana Maria Sosa Fernandez, Carmine NappiDipartimento di Scienze Ostetriche Ginecologiche Urologiche e Medicina della Riproduzione Umana, Università degli Studi “Federico II”, Napoli, Italia Abstract: The aim of this review is to define the role of the combined dienogest (DNG)/estradiol valerate (E2V) contraceptive pill, in terms of biochemistry, metabolic and pharmacological effects and clinical application as well. E2V is the esterified form of 17β-estradiol (E2), while dienogest is a fourth-generation progestin with a partial antiandrogenic effect. The cycle stability is achieved with 2 to 3 mg DNG, supporting contraceptive efficacy. In this new oral contraceptive, E2V is combined with DNG in a four-phasic dose regimen (the first two tablets contain 3 mg E2V; the next five tablets include 2 mg E2V + 2 mg DNG, followed by 17 tablets with 2 mg E2V + 3 mg DNG; followed by two tablets with 1 mg E2V only, and finally two placebo tablets). Duration and intensity of scheduled withdrawal bleeding are lower with this contraceptive pill, whereas the incidence and the intensity of intra-cyclic bleeding are similar to the other oral contraceptive. With this new pill the levels of high density lipoprotein increased, while the levels of prothrombin fragment 1 + 2 and D-dimer remained relatively unchanged; the levels of sex hormone binding globulin, cortisol binding globulin, thyroxine binding globulin increased. The most frequently reported adverse events are: breast pain, headache, acne, alopecia, migraine, increase of bodyweight. The satisfaction rate is about 79.4%.Keywords: estradiol valerate, dienogest, combined oral contraceptive, four-phasic regimen, contraceptive safety